Social media in communication of temporary organisations: role, needs, strategic perspective - Rimkunienė, Dalia; Zinkeviciute, Virgilija (Journal of Business Economics and Management, 2014)
Expansion of ”projectisation“ culture worldwide, ”internalization“ of projects and the inevitable growth of social media use globally calls for systematic and deeper insights from the strategic management viewpoint. Projects are defined as temporary organisations within various organisational bodies. In terms of the strategic management, temporary organisations are viewed as unique structural networking bodies that are anticipated to have their own strategy and management approach to meet project-based needs. Effective ”project communication“ plays a strategic role and can be an important enabler of social capital gains for organisations. Social media, as a new age phenomenon, are claimed to be the powerful mechanism that opens vast opportunities for collaborative communication. Their application in terms of temporary organisation is still underinvestigated area that lacks a researchers' attention. The aim of this research is to explore the potential of social media use in temporary organisations. The research study indicates that social media have a large potential for enhancing collaborative initiatives and collecting evidence for the strategic planning.First published online: 02 Sep 2014